The Economic Impact of Cloud Computing Diffusion in Japan - Atsushi Ozu; Norihiro Kasuga (International Telecommunications Society (ITS), 2014)
The market for cloud computing is expected to rapidly expand and change the nature of ICT across all sectors; cloud computing transforms ICT from a tool dependent upon investment and physical ownership to one that can easily make use of outside resources. In this paper, the impact of the diffusion of cloud computing on Japanese macroeconomics was estimated and analyzed utilizing a DSGE (Dynamic Stochastic General Equilibrium) model-based simulation. Its academic contributions would be summarized as follows: (1) Assuming an endogenous market structure, a model that incorporates the effects of ICT capital and the ICT investment adjustment cost was built; (2) With that model, a DSGE simulation was conducted on a system comprised of a single sector of cloud computing and then the impact of the cloud computing diffusion on Japanese macroeconomics was estimated based on the relationship between that system and the whole Japanese economy; and (3) According to the simulation results, the diffusion of cloud computing use has a 0.10% GDP boosting effect for a fast adoption case scenario (one year to steady state) and a 0.059% GDP boosting effect for a slow adoption case scenario (five years to steady state).
Keywords: 330